Assessing the measurement properties of a Frailty Index across the age spectrum in the Canadian Longitudinal Study on Aging. Issue 8 (5th July 2017) - Kanters, David M; Griffith, Lauren E; Hogan, David B; Richardson, Julie; Patterson, Christopher; Raina, Parminder
Abstract : Background: Frailty is a way to appreciate the variable vulnerability to declining health status of people as they age. No consensus for measuring frailty has been established. This study aimed to adapt a Frailty Index (FI) to the Canadian Longitudinal Study on Aging (CLSA) and evaluate its applicability in both younger and older adults. Methods: An FI was created based on 90 potential health deficits collected from adults aged 45–85 years at recruitment (N=21 241, 49.0% male). The construct validity of this instrument and the factor structure of the health deficits were evaluated. Results: The direction of associations between the FI and other variables were consistent with a priori hypotheses for construct validity. FI values were significantly associated with age (r=0.17; p<0.001), falls (r=0.12; p<0.001), injuries (r=0.12; p<0.001), formal home care (r =0.30; p<0.001), informal home care (r=0.32; p<0.001) and use of assistive devices (r=0.40; p<0.001). Values were negatively associated with male sex (r=−0.12; p<0.001), income (r=−0.34; p<0.001) and education (r=−0.17; p<0.001). Key factors among the health indicators were physical functioning, satisfaction with life and depressive symptoms. Results did not change when the sample was stratified by age and sex. Conclusion: The FI is a feasible method to evaluate frailty and capture frailty-related heterogeneity in populations aged 45–85 years. In this study, the FI had good construct validity in middle-aged and older adults, showing expected correlations with sociodemographic factors consistently across age groups. This method can be easily reproduced in similar datasets, making the FI a generalisable instrument.